2012
DOI: 10.1017/s1751731111002217
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional strategies to combat Salmonella in mono-gastric food animal production

Abstract: Nutritional strategies to minimizeSalmonellain food animal production are one of the key components in producing safer food. The current European approach is to use a farm-to-fork strategy, where each sector must implement measures to minimize and reduceSalmonellacontamination. In the pre-harvest phase, this means that all available tools need to be used such as implementation of biosecurity measures, control ofSalmonellainfections in animals at the farm as well as in transport and trade, optimal housing and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 67 publications
(66 reference statements)
0
36
0
3
Order By: Relevance
“…Fructophilic lactic acid bacteria, especially L. kunkeei, have been found to be one of the dominating bacterial species in several honeybees kept or captured in different regions [73,90]. Lactic acid bacteria have been successfully applied as probiotics to contribute to health in humans and various companion and farm animals [92,93]. As lactic acid bacteria are important components in their gastrointestinal tract, with a reported impact on the intestinal barrier mechanism [94], it is not surprising that lactic acid bacteria, especially fructophilic lactic acid bacteria, may be involved with honeybee health.…”
Section: Honey Analysis 240mentioning
confidence: 99%
“…Fructophilic lactic acid bacteria, especially L. kunkeei, have been found to be one of the dominating bacterial species in several honeybees kept or captured in different regions [73,90]. Lactic acid bacteria have been successfully applied as probiotics to contribute to health in humans and various companion and farm animals [92,93]. As lactic acid bacteria are important components in their gastrointestinal tract, with a reported impact on the intestinal barrier mechanism [94], it is not surprising that lactic acid bacteria, especially fructophilic lactic acid bacteria, may be involved with honeybee health.…”
Section: Honey Analysis 240mentioning
confidence: 99%
“…A number of feed additives have gained commercial acceptance for reducing Salmonella (Berge and Wierup, 2012). In this study, three feed additives were tested-prebiotics, probiotics, and synbiotics-by adding them to the rations fed to laying hens and broilers inoculated with S. Enteritidis.…”
Section: Resultsmentioning
confidence: 99%
“…The experiments related to these products are somewhat controversial. For example, Berge and Wierup (2012) recently reported that the challenges with nutritional interventions for Salmonella control were variable depending on the nutritional management and Salmonella status of the flock. Both probiotic and synbiotic use had limited efficacy on decreasing SE colonization although it was not certain that the microorganisms present in these products failed to colonize the enteric microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…Competitive exclusion cultures are composed of a mixture of non-pathogenic bacteria (probiotic culture) typically found in the gastrointestinal tract of the animal which are administered only in a single dose to the neonatal animal, such as the day-old chick or a newborn piglet, demonstrating the impact of the gut microbiota on gut function and disease resistance 13,14 and also that they can help to reestablish the gastrointestinal tract flora after antimicrobial treatment. 15 Because of the susceptibility of newborn animals to infection, this practice is also of commercial importance. By using this model, a number of probiotics 13,[16][17][18][19] have been shown to prevent colonization and shedding of Salmonella and Campylobacter at farm level to control food borne diseases.…”
Section: What Is a Probiotics?mentioning
confidence: 99%